The 7 Habits of Highly Effective People: Powerful Lessons in personal change - Covey, Stephen R. (London Simon and Schuster, 2020)
The 7 Habits of Highly Effective People has guided generations of readers for the past three decades. Presidents and CEO's have kept it by their bedsides and individuals of all ages and occupations have used its step-by step pathway to adapt to change and take advantage of the opportunities that change creates. This anniversary edition commemorates the wisdom of the 7 habits with fresh insight from Sean Covey.
Includes index.
Keywords: Success | Character | Physchological aspects